Discovering the mind-body connection through music as a tool for chronic pain management : a case study of psychodynamic music therapy - Salta, Maria-Eleni (2018)
Chronic pain illnesses like fibromyalgia are progressively increasing in modern world. The conventional treatments are directly influenced by the biomedical model, according to which the symptoms are suppressed and the mind is viewed as a separate entity from the body. In contrast, the bio-psychosocial model integrates all aspects of a person into a whole. Pain is viewed as an individualised condition requiring multiple facets of the human existence to be taken into account. In this case study, a client with fibromyalgia was treated in music therapy sessions for a period of twelve weeks. The collected data were analysed using Interpretive Phenomenological Analysis focusing on the meaning that the therapeutic process held for the client and the effects it had on her life and on the symptoms of pain. Psychodynamically-oriented music therapy has proven to be beneficial in the treatment of chronic pain and into promoting health, self-awareness and a better quality of life. Using music as an intervention, in collaboration with the client, an attempt was made to build a bridge between her mind and her body and to reconstruct the fragmented links between those two elements.